THE EFFECT OF GENDER ON ELEMENTARY STUDENTS' MATHEMATICAL COMMUNICATION ABILITY - Sri Winggowati; Wahyudin; Tatang Herman (Jurnal Cakrawala Pendas, 2023)
Women are often considered more talkative than men. But is it true that women have better communication skills than men? This study aims to analyze and obtain an overview of students' mathematical communication skills or called Kemampuan Komunikasi Matematis (KKM) in Bahasa Indonesia based on gender differences in comparative material. The method in this research is ex-post facto. The subjects in this study were 6th grade students at an elementary school in the city of Bandung with a total of 27 boys and 35 girls. The research instrument used was a test of mathematical communication skills (KKM), which measures the ability to solve word problems on comparative material. Data analysis in this study to see the mean difference test between the scores of mathematical communication skills (KKM) based on gender. The results of this study concluded that there was no difference in the effect of gender (male and female) on mathematical communication skills (KKM). Women and men have the same potential to have mathematical communication skills while practicing and learning. The results of this study can be used as a basis for educators to train mathematical communication skills to students in elementary schools fairly. Perempuan kerap kali dianggap lebih cerewet dibanding laki-laki. Tapi benarkah bahwa perempuan memiliki kemampuan komunikasi matematis yangg lebih baik dibanding laki-laki? Penelitian ini bertujuan untuk menganalisis dan memperoleh gambaran tentang kemampuan komunikasi matematis(KKM) siswa berdasarkan perbedaan jenis kelamin pada materi perbandingan. Metode dalam penelitian ini adalah ex-post facto.Subjek pada penelitian ini adalah siswa kelas 6 di sebuah sekolah dasar di Kota Bandung dengan jumlah, 27 orang laki-laki dan 35 orang perempuan. Instrumen penelitian yang digunakan berupa soal tes kemampuan kemampuan komunikasi matematis (KKM), yang mengukur kemampuan menyelesaikan soal cerita pada materi perbandingan.Analisis data pada penelitian ini untuk melihat uji perbedaan rerata antara skor kemampuan komunikasi matematis (KKM) berdasarkan jenis kelamin.Hasil penelitian ini disimpulkan bahwa tidak terdapat perbedaan pengaruh jenis kelamin (laki-laki dan perempuan) terhadap kemampuan komunikasi matematis (KKM). Perempuan maupun laki-laki berpotensi yang sama besar memiliki kemampuan komunikasi matematis selama berlatih dan berusaha. Hasil penelitian ini dapat dijadiakan landasan bagi para pendidikan untuk melatihkan kemampuan komunikasi matematis secara adil kepada siswa di sekolah dasar.